2020
DOI: 10.1039/c9ra09082g
|View full text |Cite
|
Sign up to set email alerts
|

Partially charged platinum on aminated and carboxylated SBA-15 as a catalyst for alkene hydrosilylation

Abstract: Ptδ+ was uniformly dispersed in aminated and carboxylated SBA-15 as a highly efficient catalyst for the hydrosilylation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The only product in this case was compound 5a, which was formed in 78.5% yield (Table 2, entry 18). The addition of phosphine ligands also reduced the overall product yields, which ranged from 0 to 60% (Table 2, entries [19][20][21][22][23][24][25][26]. The addition of bidentate ligands almost deactivated the catalytic system (Table 2, entries [23][24][25][26].…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The only product in this case was compound 5a, which was formed in 78.5% yield (Table 2, entry 18). The addition of phosphine ligands also reduced the overall product yields, which ranged from 0 to 60% (Table 2, entries [19][20][21][22][23][24][25][26]. The addition of bidentate ligands almost deactivated the catalytic system (Table 2, entries [23][24][25][26].…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…1–3 Despite significant efforts spent in the development of nonprecious metal catalytic systems and progress made in this direction, platinum complexes remain commonly used catalysts for hydrosilylation processes. 4–29 However, platinum-catalyzed hydrosilylation has difficulties in controlling catalyst performance and insufficiently high selectivity of the process, which affect the overall costs of product formation. A better understanding of the catalytic reaction mechanism can provide a rational solution to these problems.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of a novel bifunctional heterogeneous catalyst using mesoporous silica of type SBA-15 (Pt 2+ /SBA-APTE-SA) was investigated. 24 The catalyst was completed with the functionalization of silica with (3-aminopropyl)triethoxysilane (APTES), succinic anhydride (SA), and a partial positively charged Pt 2+ . The prepared catalyst possesses superior catalytic activity toward the hydrosilylation of 1,1,1,3,5,5,5-heptamethyltrisiloxane (MDHM) with allyloxy polyethylene glycol (APEG) compared with a heterogeneous Pt-catalyst.…”
Section: Silica-based Nanomaterials In Advanced Catalysismentioning
confidence: 99%
“…This catalyst shows future application as a green hydrosilylation process for the industry. 24 In the presence of N-hydroxyphthalimide (NHPI), another approach demonstrated that Co 2+ -salen complex catalysts-modied silica was investigated and used for the aerobic oxidation of alkyl aromatics at atmospheric pressure shown in Fig. 4a.…”
Section: Silica-based Nanomaterials In Advanced Catalysismentioning
confidence: 99%
“…[43] The decrease in surface area and pore volume of Fe 3 O 4 @mSiO 2 -APTES-Pt is due to blockage of micropores by Pt and the amino ligands. [36,44] Figure 3 showed the XRD patterns of both the supports and catalysts of the porous and magnet porous particles. The diffraction peaks at 2θ = 30.4 , 35.8 , 43.5 , 53.9 , 57.5 , and 63.2 are observed in the spectrum of Fe 3 O 4 , which can be ascribed to diffraction peaks of (220), (311), (400), ( 422), (511), and (440) planes of cubic Fe 3 O 4 (JCPDS No.…”
Section: Catalysts Characterizationmentioning
confidence: 99%